Multidimensional comparative evaluation of first-line therapies for extensive-stage small cell lung cancer: a systematic review and network meta-analysis of clinical efficacy and safety profiles - Ziyao Jiang; Fangrui Zhao; Butuo Li; Junyi He; Huiwen Yang; Yuhan Ji; Bing Zou; Jinming Yu; Linlin Wang (BMC Cancer)
Abstract Background The first-line treatment for extensive-stage small cell lung cancer (ES-SCLC) has evolved from chemotherapy alone to chemoimmunotherapy. However, the improvements in overall survival (OS) and progression-free survival (PFS) have been modest. Therefore, this study employs a comprehensive multidimensional evaluation framework to identify optimized therapeutic combinations with enhanced efficacy and improved safety profiles in the immunotherapy era. Methods An adaptive search strategy was employed to retrieve all relevant literature from electronic databases, including PubMed, Embase, Web of Science, and the Cochrane Library, from database inception to November 2024. The retrieved studies were carefully screened according to pre-designed inclusion and exclusion criteria. Clinical research articles and their supplementary materials that met the criteria were obtained and thoroughly reviewed. Manual data extraction was conducted, with the safety data and efficacy outcomes. A network meta-analysis of all acquired data for each outcome was performed. The study protocol was pre-registered in PROSPERO, CRD42024612944. Results This network meta-analysis included 6,473 patients from 14 head-to-head randomized controlled trials (RCTs). Compared with etoposide-platinum chemotherapy combined with a programmed cell death ligand 1 inhibitor (the Chemo + PD-L1 regimen), the addition of anlotinib (the Chemo + PD-L1 + Anlo regimen) resulted in better PFS (hazard ratio (HR), 0.42; 95% confidence interval (CI), 0.33–0.54) and objective response rate (ORR) (odds ratio (OR), 1.81; 95% CI, 1.13–2.91). Moreover, adding BMS-986012 (anti-fucosyl-GM1 antibodies) to the Chemo + PD-L1 regimen ranked first in the surface under the cumulative ranking curve (SUCRA, 0.96) analysis for OS. Compared with the Chemo + PD-L1 regimen, the addition of an anti-CTLA-4 inhibitor (the Chemo + PD-L1 + CTLA-4 regimen) was associated with an increased risk of treatment-related adverse events (TRAEs) of grades ≥ 3 (risk ratio (RR), 1.19; 95%CI, 1.04–1.36). Conclusions Incorporating anlotinib into the Chemo + PD-L1 regimen can be a viable first-line option for patients with high tumor burden, but cannot fully replace the current first-line standard-of-care (SOC). Chemoimmunotherapy combined with immune-related targeting drugs demonstrates the potential to improve overall survival.